2004
DOI: 10.1128/iai.72.4.2214-2221.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization ofAncylostoma ceylanicumKunitz-Type Serine Protease Inhibitor: Evidence for a Role in Hookworm-Associated Growth Delay

Abstract: Hookworm infection is a major cause of iron deficiency anemia and malnutrition in developing countries. The Ancylostoma ceylanicum Kunitz-type inhibitor (AceKI) is a 7.9-kDa broad-spectrum inhibitor of trypsin, chymotrypsin, and pancreatic elastase that has previously been isolated from adult hookworms. Site-directed mutagenesis of the predicted P1 inhibitory reactive site amino acid confirmed the role of Met 26 in mediating inhibition of the three target serine proteases. By using reverse transcription-PCR, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 61 publications
2
42
0
Order By: Relevance
“…ceylanicum [18,34], these kunitz-type inhibitor domains have been predicted to have an essential role in nematode development, a role also envisaged for this domain in the BLI-5 orthologues described in this study.…”
Section: Discussionsupporting
confidence: 53%
“…ceylanicum [18,34], these kunitz-type inhibitor domains have been predicted to have an essential role in nematode development, a role also envisaged for this domain in the BLI-5 orthologues described in this study.…”
Section: Discussionsupporting
confidence: 53%
“…For example, if AceES-2 is a virulence factor that has a role in bloodfeeding, neutralization of its function might be expected to have a greater effect on anemia than on weight loss (assuming that the worms continue to survive with reduced feeding efficiency). Conversely, it has recently been demonstrated that vaccination with the Kunitz inhibitor AceKI leads to improved weight gain but has little effect on anemia (22), which is consistent with the demonstrated activity of this protein against host digestive enzymes (47). Together, these results suggest that the pathogenesis of hookworm anemia and growth delay are due to distinct molecular mechanisms and that vaccination against specific virulence factors may allow these disease parameters to be experimentally decoupled.…”
Section: Discussionmentioning
confidence: 54%
“…As the human hookworm A. duodenale is both orally infective as well as infective through the percutaneous route, this approximates a natural route of infection. More importantly, this model reproduces weight and blood loss that result from human infection with A. duodenale.In addition to modeling the host-parasite relationship for human hookworm infection, the hamsters have been used with some success for investigating protective immunity from a new generation of recombinant anti hookworm vaccines (2,8,9,13,22,33). However, detailed immunological investigations have not been conducted in this model due of the lack of available immunological reagents.…”
mentioning
confidence: 99%